A Personal Reflection on 40 Years of Radiocarbon Dating and Archaeology1. Issue 5 (29th December 2016) - Van Strydonck, Mark
Abstract: In 1981, the first 14 C and Archaeology Symposium was organized because it was felt necessary to have a symposium that focused on the specific problems related to the use of 14 C dating in archaeology. The dating method has been constantly changing and approving itself technically as well as in the application of the method. The relationship between the archaeologists and the 14 C dating laboratories has, however, never been straightforward. For a lot of 14 C laboratories, archaeology was not their core business. For archaeologists, the main problem arose from an insufficient knowledge of natural sciences. The last decennia, however, 14 C and archaeology are growing towards one another. One of the reasons might be the introduction of small exclusively 14 C-dedicated machines and the availability of fully automatic graphitization lines.